Caracterização da placa bipolar de eletrolisadores alcalinos para produção de hidrogênio - Balbuena, Victor Alejandro Rivarola (2021)
The current unprecedented environmental situation due to negative climate change impacts has accelerated the development of technologies towards the imminent energy transition from fossil fuels to carbon free renewable fuels. Hydrogen (H2) technologies are promissory to head the economy decarbonization on the energy transition. The Brazilian energy mix allows the country the potential for producing green Hydrogen from renewable sources. In this context, the Itaipu Technological Park (PTI) works on gas production, storage and applications researches at the Hydrogen Production Plant (PPH) installed at the PTI, using alkaline electrolyzer technology. To reduce technology cost, material characterization of the bipolar electrolyzer installed at the PPH are carried out to nationalize the technology. The present work proposes a characterization of the bipolar plate of the alkaline electrolyzer using chemical and electrochemical techniques. The bipolar plate is one of the internal components that allows the construction of state-of-theart alkaline electrolyser technologies. As a result, it was identified by X-ray diffraction (XRD) and X-ray energy dispersive (EDS) techniques that the bipolar plate consists of a NiFe alloy. Images obtained by scanning electron microscopy (SEM) demonstrated that the bipolar plate is a nickel-plated steel for corrosion resistance. Using the Brunauer-Emmett-Teller (BET) method, a specific surface area of 5.08 gr/m² was calculated. By Cyclic voltammetry analysis, the nickel voltametric profile of the bipolar plate was identified. Increasing the temperature to 80°C shows an increase of up to 27 times the current density for O2 production and up to 25 times for H2 production. This increase agreed with charge transfer resistance reduction seen by electrochemical impedance spectra (EIS) when increasing temperature. The O2 evolution reaction performed better than H2 when compared EIS results by passing a cathodic and anodic current density of 10 mA/cm2.